INOVASI DALAM PENANGANAN PENYAKIT TIDAK MENULAR DI KOTA MEDAN: PROMOSI GAYA HIDUP SEHAT DAN PEMANTAUAN BERKALA - LESMANA SYAHRIR (JURNAL ILMIAH KOHESI, 2023)
The residents of Medan City have not been able to increase efforts in preventing the occurrence of non-communicable disease infections caused by unhealthy lifestyles and lack of regular health checks or checks. This study used descriptive analytical method. The population of this study amounted to 3,200 residents affected by non-communicable diseases who were hospitalized in Medan City, where the samples taken amounted to 61 residents affected by non-communicable diseases who were hospitalized in Medan City. The results of the study explained that the population affected by many non-communicable diseases is residents in Medan Kota District in the age range of 15-20 years, where these non-communicable diseases arise due to not following a healthy lifestyle by eating foods that have nutrients and have not been carried out regular full-body examinations.